Chitosan films incorporated with nettle (Urtica Dioica L.) extract-loaded nanoliposomes: II. Antioxidant activity and release properties. (3rd July 2016) - Almasi, Hadi; Zandi, Mohsen; Beigzadeh, Sara; Haghju, Sara; Mehrnow, Nazila
Abstract: Chitosan films were loaded with NE nettle ( Urtica dioica L. ) extract (NE) at concentrations of 0, 0.5, 1 and 1.5%w/w in the free or nanoliposomal form to obtain active and nanoactive films, respectively. The antioxidant potential of the films containing NE-loaded nanoliposomes was decreased in comparison of free NE incorporated films. Diffusion of NE to soybean oil was enough to delay the induction of the oxidation of soybean oil stored for 60 days in contact with chitosan based films. Release studies indicated that the release rate of NE in 95% ethanol simulant significantly decreased by the nanoencapsulation of NE. The diffusion coefficient (D) for chitosan films containing 1.5%w/w of free and encapsulated NE at 25 °C was 18.80 and 3.68 × 10 −7 cm 2  s −1, respectively. Moreover, the formation of nanoliposomes diminished the increasing effect of temperature on the release rate as when storage temperature increased from 4 °C to 40 °C.